2023
DOI: 10.3390/nu15153430
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Vitamin D in Respiratory Tract Infections and COVID-19 in Children

Maria Nicolae,
Cristina Maria Mihai,
Tatiana Chisnoiu
et al.

Abstract: Acute respiratory tract infections (ARTIs) are one of the main reasons that the pediatric population goes to the doctor. The connection between ARTI and vitamin D (VD) is currently debated by the medical community, and so far, there has been little agreement with regard to the ideal level of 25(OH)D concentration that would provide protection for the respiratory tract, or the effectiveness of its administration in the treatment of respiratory infections. The purpose of this literature review was to bring atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 89 publications
(127 reference statements)
0
5
0
1
Order By: Relevance
“…All these three findings taken together are consistent with the findings of the bulk of systematic reviews and meta-analyses of observational studies and randomized clinical trials, which outlined an increased risk of SARS–CoV–2 infection and/or complications in patients with low vitamin D levels [ 10 , 13 , 15 , [32] , [33] , [34] , [35] , [36] ], even though the link between VDD and SARS–CoV–2 associated mortality is still elusive [ 33 , 34 ]. Vitamin D plays a crucial role of immunomodulator through the improvement of components of the host’s innate and adaptive immune response and downregulation of the SARS-CoV-2 associated inflammatory cascades [ 37 , 38 ]. Several mechanisms of action through which vitamin D exerts its anti-SARS–CoV–2 effects have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these three findings taken together are consistent with the findings of the bulk of systematic reviews and meta-analyses of observational studies and randomized clinical trials, which outlined an increased risk of SARS–CoV–2 infection and/or complications in patients with low vitamin D levels [ 10 , 13 , 15 , [32] , [33] , [34] , [35] , [36] ], even though the link between VDD and SARS–CoV–2 associated mortality is still elusive [ 33 , 34 ]. Vitamin D plays a crucial role of immunomodulator through the improvement of components of the host’s innate and adaptive immune response and downregulation of the SARS-CoV-2 associated inflammatory cascades [ 37 , 38 ]. Several mechanisms of action through which vitamin D exerts its anti-SARS–CoV–2 effects have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a few studies reported no or an inconsistent relationship between vitamin D deficiency and COVID–19 related infection, intensive care unit admission, length of hospital stay, ventilator support requirement, and mortality [ 12 , 13 , 17 , 18 , [42] , [43] , [44] , [45] ]. Moreover, the benefit of vitamin D supplementation is still elusive in social groups such as children [ 38 ]. Differences in design, definitions used for vitamin D deficiency, methodological quality, and populations of individual studies included in these systematic reviews and meta-analyses could explain discrepancies in conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, Şişmanlar et al’s case–control study [ 30 ] found no significant correlation between vitamin D levels and the incidence or severity of lower respiratory tract infections despite a widespread prevalence of vitamin D deficiency/insufficiency among the children studied. On the contrary, Nicolae et al [ 31 ], through a literature review, highlighted the potential immunomodulatory and antiviral effects of vitamin D, suggesting that its supplementation might lower the risk of acute respiratory tract infections, including COVID-19. While Şişmanlar et al caution against assuming the direct protective role of vitamin D against such infections due to their findings, Nicolae et al advocate for the potential benefits of vitamin D in mitigating the severity of RTIs, urging further research to solidify these preliminary observations.…”
Section: Discussionmentioning
confidence: 99%
“…Признано, что патогенность респираторных вирусов, таких как COVID-19 или грипп, может быть связана с гиперцитокинемией или цитокиновым штормом, потенциально фатальным самовоспроизводящимся циклом воспалительных реакций [28,29]. При инфицировании вирусом гриппа отмечено снижение уровней провоспалительных «штормовых» интерлейкинов -IFN-β, TNF-α, IL-8, IL-6, RANTES в эпителиальных клетках легких в ответ на лечение витамином D [30].…”
Section: бронхопульмонология и отоларингологияunclassified